2022
DOI: 10.3389/feduc.2021.744388
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an SEL Program in a Diverse Population of Low Achieving Secondary Education Students

Abstract: Adolescents’ social-emotional skills are associated with positive outcomes in psychosocial health and success in education and work. In this study, we examined the effectiveness of Skills4Life, a Social Emotional Learning program for preparatory vocational secondary education aimed at enhancing self-awareness, social awareness, self-management, relationship skills, and responsible decision making. Low-achieving students with additional educational needs participated in a quasi-experimental study, with an inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 67 publications
(77 reference statements)
1
4
0
2
Order By: Relevance
“…Specifically, existing research showed the efficacy of SEL programs in enhancing SEL competencies for kindergarten children [ 46 ], primary school students [ 45 ] secondary school students [ 47 ], and high school students [ 26 ]. Furthermore, our findings are in line with studies showing positive effects of SEL programs on students’ self-management skills [ 48 ], well-being (positive attitude, prosocial behavior, and academic performance) [ 26 ], social awareness [ 23 ], social skills and empathy [ 49 ]. The results of the present study support the importance of addressing socio-emotional skills and psychosocial difficulties in school intervention programs with students.…”
Section: Discussionsupporting
confidence: 90%
“…Specifically, existing research showed the efficacy of SEL programs in enhancing SEL competencies for kindergarten children [ 46 ], primary school students [ 45 ] secondary school students [ 47 ], and high school students [ 26 ]. Furthermore, our findings are in line with studies showing positive effects of SEL programs on students’ self-management skills [ 48 ], well-being (positive attitude, prosocial behavior, and academic performance) [ 26 ], social awareness [ 23 ], social skills and empathy [ 49 ]. The results of the present study support the importance of addressing socio-emotional skills and psychosocial difficulties in school intervention programs with students.…”
Section: Discussionsupporting
confidence: 90%
“…One of the actions of the approaches done by the teacher is directing the less focused student. The affective and social-emotional approaches are commonly used in a diverse classroom especially for less motivated and low-achieving students (Busse et al, 2020;Van De Sande et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the science teachers in Banjarnegara, Indonesia, have moderately positive attitudes toward teaching diverse students in general classrooms; they have personal experiences in interacting with special educational needs students (Atika et al, 2022). A social-emotional learning program was carried out for preparatory Dutch vocational secondary education in a diverse population of low-achieving students (Van De Sande et al, 2022). Distinct strategies, media, methods, and attitudes are employed by the teachers, a special program is also offered by the school, to respond to a certain case of students' diversity.…”
Section: Introductionmentioning
confidence: 99%
“…To explore the associations between different social-emotional skills and psychosocial health variables, we conducted an exploratory cross-sectional study. For this, we used baseline data (N = 796) from a longitudinal study on the effects of the Dutch S4L program adapted to the needs of PVSE students (Van De Sande, 2022). The data used in this study are available at https://doi.org/ 10.17026/SS/DNOJRU.…”
Section: Methodsmentioning
confidence: 99%